2000
DOI: 10.1099/00207713-50-2-873
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium akagii sp. nov. and Clostridium acidisoli sp. nov.: acid-tolerant, N2-fixing clostridia isolated from acidic forest soil and litter.

Abstract: Two anaerobic acid-tolerant bacteria, CK58T and CK74 T , were isolated from acidic beech litter and acidic peat-bog soil, respectively. Both bacteria were spore-forming, motile rods with peritrichous flagella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 53 publications
3
40
0
7
Order By: Relevance
“…1a), formed multicellular aggregates and sometimes displayed connecting filaments ( Fig. 1b) (Kuhner et al, 2000;Matthies et al, 2001;Küsel et al, 2001); outer and cytoplasmic membranes were observed ( T were also sometimes tethered by connecting filaments (Fig. 1d), had a three-layered cell wall ( Fig.…”
Section: Morphological and Cytological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a), formed multicellular aggregates and sometimes displayed connecting filaments ( Fig. 1b) (Kuhner et al, 2000;Matthies et al, 2001;Küsel et al, 2001); outer and cytoplasmic membranes were observed ( T were also sometimes tethered by connecting filaments (Fig. 1d), had a three-layered cell wall ( Fig.…”
Section: Morphological and Cytological Characteristicsmentioning
confidence: 99%
“…Acetate is a common product of fermenters (e.g. Bulthuis et al, 1991;Schlegel & Jannasch, 1992;Kuhner et al, 2000), and is a substrate for denitrifiers such as ED1…”
Section: The Denitrifiers Ed1mentioning
confidence: 99%
“…Cell-free extracts were prepared under anoxic conditions (Kuhner et al, 2000). Membranous and cytoplasmic fractions were prepared under oxic conditions (Fröstl et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Electron micrographs were obtained with a Zeiss CEM 902A (Oberkocken, Germany) (Gößner et al, 1999, Kuhner et al, 2000; cells were negatively stained with uranyl acetate (Valentine et al, 1968). Growth was measured as OD 660 ; the optical path width (inner diameter of culture tubes) was 1?6 cm.…”
mentioning
confidence: 99%
“…Funke et al (1997) described a coryneform bacterium with filaments. Kuhner et al (2000) and Matthies et al (2001) studied anaerobic clostridia from acidic forest bog locations and suggested these appendages to serve as electron transport system.…”
Section: Filamentsmentioning
confidence: 99%